A Note on the Cobb-Douglas Function - Simon, Herbert A.; Levy, Ferdinand K. (Review of Economic Studies, 1963)
Herbert A. Simon, Ferdinand K. Levy; A Note on the Cobb-Douglas Function, The Review of Economic Studies, Volume 30, Issue 2, 1 June 1963, Pages 93–94, https://